Ø·Ø±ÙŠÙ‚Ø© ØªØ¯Ø±ÙŠØ³ Ø§Ù„Ù†ØµÙˆØµ Ø§Ù„Ø£Ø¯Ø¨ÙŠØ© Ø§Ù„Ù…Ø«Ø§Ù„ÙŠØ© ÙÙŠ Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ§ - Fahrurrazi, Fahrurrazi (SCAD Independent, 2014)
The method used by the teacher is one of the reasons that led to the success in the learning process. Therefore the method is one of the pillars in education. It has been proven that a good and appropriate way it can assist teachers in addressing gaps in the implementation of the curriculum, can also facilitate students in understanding the subject matter, and can detect weaknesses of students in learning Arabic literary texts, thus can find a solution to solve it. So also with teaching Arabic literary texts to the students, teachers should use appropriate methods in teaching it, so that the students easy to understand explanation of the teacher. Therefore, researchers have taken the title of this study is